KARAKTERISTIK KIMIAWI DAN MIKROBIOLOGI KEFIR SUSU SAPI DENGAN PENAMBAHAN SUSU KEDELAI - Julianto, Budi; Rossi, Evy; ', Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to observe chemical and microbiology characteristic of three kind of kefir, made from cow milk with addition of soymilk. Observed kefirs were kefir whey (KW), kefir optima (KO), and kefir prima (KP). A Completely Randomized Design (CRD) was used in this research with six treatments and three replications treatment consists of KW1 (100% cow milk), KW2 (50% cow milk: soymilk 50%), KO1 (100% cow milk), KO2 (50% cow milk: 50% soymilk), KP1 (100% cow milk), and KP2 (50% cow milk: 50% soymilk). The results showed that the cow milk with soymilk significantly affected the degree of acidity (pH), total lactic acid bacteria, total lactic acid, total yeast, and alcohol content.   Keywords : Kefir, cow milk, soymilk, lactic acid bacteria, yeast.